KAJIAN KOTA LAYAK PEMUDA KOTA SEMARANG - Isti Hidayah; Suwito Eko Pramono; Satya Budi Nugraha (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
Youth is the backbone of the future of development. Indonesia's youth potential spread from Sabang to Merauke needs integrated management. This is what underlies the Government, through the Ministry of Youth and Sports (Kemenpora), proclaiming a program of Regency /City Fit for Yotuh which is outlined in the Regulation of the Minister of Youth and Sports No. 11 of 2017. The city of Semarang as one of the major cities in Central Java is still in the progress of development, is expected to participate in becoming one of the Cities fit for Youth in Indonesia. Therefore this research was conducted to study the feasibility of Semarang as a City Fit for Youth. This study uses a mixed method, which combines quantitative and qualitative methods. Data sources used are primary data and secondary data. Primary data is obtained by field surveys using data collection methods directly on data sources, through field surveys and interviews. While secondary data is obtained from documents or data from an institution or agency. The results showed that youth activities in Semarang City consisting of youth awareness activities, youth empowerment and youth development were carried out in Semarang City. These activities are the result of the organization agencies (OPD), educational institutions and private companies that target youth, high school students, students and santri and involve various related institutions and are supported by funding from the APBN, APBD, BUMN, Foundation, Private and Communities. From the conditions of the implementation of activities and the availability of youth infrastructure, the City of Semarang was considered quite feasible to become one of the Youthful Cities in Indonesia.x